PENGARUH JENIS LEMAK DAN MINYAK NABATI PADA PROSES EKSTRAKSI SISTEM ENFLEURASI TERHADAP KARAKTERISTIK MINYAK ATSIRI BUNGA KAMBOJA CENDANA (Plumeria alba) - Patrisia, Sasha; Wartini, Ni Made; suhendra, lutfi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 5 No 2 (2017): April, 2017)
The extraction of enfleurage system is widely used to take volatile compounds in flowers. The purposes of this research were to know the influence of fat and vegetable oil in the extraction process of enfleurage system on sandalwood frangipani flower’s essential oil characteristic, and to determine the best combination of fat and vegetable oil that produced essential oil of sandalwood frangipani flower. This research was a factorial research which used Randomize Block Design with 2 factors. The first factor was the type of fat oil, which consist of butter and margarine. The second factor was the type of vegetable oil, which consist of coconut, palm, corn, and soy oil, so there were 8 combination of experiments. The experiments were done in two replications, resulting 16 units of experiment. The variables observed were rendement of essential oil, density, solubility in alcohol, and aroma preference. The objective data were analyzed by analysis of variance and then continuing by Duncan test. Meanwhile, aroma preference data were analyzed by using Friedman test. The best treatment were determined using effectiveness index test. The result showed that there was a significant influence of fat and vegetable oil on essential oil’s rendement and solubility in alcohol, but there was no significant effect on essential oil’s aroma preference. Combination treatment of butter and corn oil was the best treatment that produced essential oil of sandalwood frangipani flower with rendement, density, and solubility in alcohol was 4.13%, 0.83 g/ml, and 6.5 ml, respectively. The aroma preference of this product was in the range of ‘quite like’ to ‘like’. Keywords: enfleurage, sandalwood frangipani flower, fat oil, vegetable oil, Plumeria alba.